2022
DOI: 10.3390/nu14040795
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Restricted versus Liberal Early Fluid Volumes on Plasma Sodium, Weight Change, and Short-Term Outcomes in Extremely Preterm Infants

Abstract: The optimal fluid requirements for extremely preterm infants are not fully known. We examined retrospectively the fluid intakes during the first week of life in two cohorts of extremely preterm infants born at 22–26 weeks of gestation before (n = 63) and after a change from a restrictive to a more liberal (n = 112) fluid volume allowance to improve nutrient provision. The cohorts were similar in gestational age and birth weight, but antenatal steroid exposure was more frequent in the second era. Although fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, some studies have established a lack of a strong correlation between early fluid restriction in preterm neonates and BPD [25]. Koo et al found that there is no significant association between early fluid restriction and BPD [26].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies have established a lack of a strong correlation between early fluid restriction in preterm neonates and BPD [25]. Koo et al found that there is no significant association between early fluid restriction and BPD [26].…”
Section: Discussionmentioning
confidence: 99%